Identifikasi Kemampuan Literasi Sains Peserta Didik Kelas VIII SMPN se-Sungguminasa - Arsyad, Arie Arma; Sartika, Dewi (Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to describe the level of scientific literacy abilities of class VIII students at SMPN Sungguminasa for the 2023/2024 academic year in the aspect of scientific competence on the subject matter of the human excretory system. The research population of class VIII students at SMPN throughout Sungguminasa was 1489 students, the research sample was 400 students with a sampling technique using the Slovin formula. The research instrument consisted of 20 scientific literacy test questions. Data collection techniques by administering multiple-choice tests. Data were analyzed using descriptive statistical analysis. The research results showed that the level of scientific literacy ability of class VIII students at SMPN throughout Sungguminasa was in the low category with an average of 9.32.